Influence of the Substrate Material on the Formation and Properties of Micro-Arc Coatings with Particles of β-Tricalcium Phosphate; Russian Physics Journal; Vol. 65, iss. 6 - Sedelnikova M. B. Maria Borisovna; Ugodchikova A. V. Anna Vladimirovna; Uvarkin P. V. Pavel Viktorovich; Sharkeev Yu. P. Yury Petrovich; Khimich M. A. Margarita Andreevna; Tolkacheva T. V. Tatjyana Viktorovna; Chebodaeva V. V. Valentina Vadimovna; Khlusov I. A. Igor Albertovich; Schmidt J. Jurgen (2022, 2022)
Title screen